2014
DOI: 10.1111/aos.12597
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of retinal vessels in eyes with retinitis pigmentosa by retinal oximeter

Abstract: ABSTRACT.Purpose: To study changes in the oxygen saturation and calibre of retinal vessels in the eyes of patients with retinitis pigmentosa (RP). Method: In this cross-sectional study, 63 eyes of 63 patients with RP and 14 eyes of 14 healthy subjects were enrolled and examined at Toyama University Hospital. Retinal oximetry measurements were performed using a spectrophotometric oximetry unit (Oxymap T1, Reykjavik, Iceland), which is coupled to a fundus camera base (TRC-50DX; Topcon Corporation, Tokyo, Japan).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 21 publications
8
21
0
Order By: Relevance
“…; Ueda‐Consolvo et al. ; Zong et al. ), we found once more an increased A‐SO 2 and even more, an increased V‐SO 2 , with corresponding decrease in the A‐V SO 2 values within the rod‐cone dystrophy (RCD) group (Bojinova et al.…”
Section: Materials and Methods (Described In Details: Türksever Et Almentioning
confidence: 70%
“…; Ueda‐Consolvo et al. ; Zong et al. ), we found once more an increased A‐SO 2 and even more, an increased V‐SO 2 , with corresponding decrease in the A‐V SO 2 values within the rod‐cone dystrophy (RCD) group (Bojinova et al.…”
Section: Materials and Methods (Described In Details: Türksever Et Almentioning
confidence: 70%
“…These researchers found that younger RP patients presented with higher AS and AVS, whereas older RP patients lower presented with AS and AVS (39). Ueda‐Consolvo and collaborators proposed that the severity of RP correlates with elevated oxygen saturation in the VS and decreased retinal vessel calibers (44).…”
Section: Discussionmentioning
confidence: 99%
“…Geirsdottir, et al used the Oxymap T1 to demonstrate that oxygen saturation in retinal veins decreases with age in healthy eyes [12]. Several studies have found reduced oxygen saturation values in occluded arteries and veins [1417] and increased venous oxygen saturation in patients with exudative age-related macular degeneration (AMD) [18], advanced primary open-angle glaucoma [1921], diabetic retinopathy[2224], and retinitis pigmentosa [25, 26]. For patients with retinitis pigmentosa, increased arterial oxygenation saturation and increased arteriovenous oxygen saturation differences have been observed, with age seemingly affecting these values [27, 28].…”
Section: Introductionmentioning
confidence: 99%